Komisaris Independen sebagai Pemoderasi Faktor-Faktor yang Mempengaruhi Earnings Response Coefficient - Syafira Ulya Firza; Suriani Ginting (Fakultas Bisnis Universitas Mikroskil, 2022)
This research aims to examine and analyze the factors that can affect the Earnings Response Coefficient and how the role of the Independent Commissioner in moderating the relationship between these factors and the Earnings Response Coefficient. The object of this research was on companies listed on the Indonesia Stock Exchange during the 2019-2021 period. The population in this study amounted to 783 companies. The sampling method used was the purposive sampling method and obtained a sample of 244 companies with a total of 732 observations. The data analysis method used was Partial Least Square with a two-stage approach model using the SmartPLS 3 statistical software tool. The results showed that the variable Disclosure of Corporate Social Responsibility, Earnings Management, Growth Opportunities, Default Risk, and Profitability has no significant effect on the Earnings Response Coefficient of companies listed on the Indonesia Stock Exchange for 2019-2021 period. In addition, the moderation test shows that the Independent Commissioner can't moderate the relationship between Disclosure of Corporate Social Responsibility, Earnings Management, Growth Opportunities, Default Risk, and Profitability with Earnings Response Coefficient in companies listed on the Indonesia Stock Exchange for the 2019-2021 period.